Effects of job stress and emotional intelligence on job performance of employees - Dizer, Yiğit (My University, 2019)
Bu çalışma iş kaynaklı stresin ve duygusal zekanın çalışanların iş performansı üstündeki etkilerini araştırmaktadır. Yıllar ilerledikçe stres ve duygusal zeka organizasyonlarda performansı etkileyen en önemli unsurlar olmaya başladılar. Olumlu ya da olumsuz da olsa stres bir organizasyonun yönetiminde ele alınmalıdır. Çünkü stres direk olarak çalışanların davranışlarını, birbirleri arasındaki ilişkilerini ve yeteneklerini etkilemektedir. Bu nedenle çalışanların iş performansı stres tarafından etkilenmektedir. Duygusal zeka da organizasyonlarda son yıllarda çalışan performansına çok önemli katkıları olmasından dolayı çalışanlarda yüksek olması beklenen bir kavram olarak ele alınmaktadır. Bu kapsamda, stresin ortaya çıkma nedenleri, stresin aşamaları, iş stresinin etkileri, stresle baş etme yöntemleri, duygusal zeka konsepti, duygusal zekanın çalışanların karakteristik özelliklerindeki kabiliyetleri ve tüm bunların iş performansına etkileri detaylı bir şekilde açıklanmıştır. FMCG sektöründe çalışan 200 kişiye uygulanan anketlerle stres ve duygusal zekanın çalışanların iş performansı ile ilişkisinin sonuçları gözlemlenmiştir.

This study investigates the relationship between job related stress and emotional intelligence with the job performance of employees. Over the years, stress and emotional intelligence have become the most important factors affecting performance in organizations. Positive or negative, stress should be discussed in management of an organization. Because stress directly impresses the behaviours, relationships and capabilities of employees. For that reason, employees’ job performances are influenced by job stress. Emotional intelligence has also started to be considered as a concept that is expected to be high in employees because of significant contributions to employee performance inside organizations in the recent years. In this research, elements which arise the stress, phase of stress, effects of job stress, handle with job stress, emotional intelligence concept, emotional intelligence’s capabilities on employees’ characteristics and their effects to the job performance were deeply explained. Questionnaires were applied to 200 employees in FMCG sector to observe the results of relationship between job stress and emotional intelligence with the job performance of employees.
Keywords: Duygusal zeka; Emotional intelligence; İş Performansı Job Stress; İş stresi; Job Performance; Job stress